Association between IFNGR1 gene polymorphisms and tuberculosis susceptibility: A meta-analysis - Liwei Cheng; Fan Zhang; Ying Wang; Jing Chen; Xiaoping Yuan (Frontiers Media S.A., 2022)
The association of IFN-γ receptor 1 (IFNGR1) gene polymorphisms with tuberculosis (TB) susceptibility has not been systematically studied. We therefore conducted a meta-analysis to assess their association. Literature search was conducted in PubMed, EMBASE, Web of Science, and the Cochrane Library. Odds ratio (OR) and 95% confidence interval (CI) was pooled by the random-effect model. Statistical analyses were performed using STATA 12.0 software. Fourteen studies involved 7,699 TB cases and 8,289 controls were included in this meta-analysis. A significant association was found between the IFNGR1 rs2234711 polymorphism and TB susceptibility among Africans in dominant model (OR = 1.24, 95%CI:1.01-1.52), and among Asians in allele model (OR = 0.89, 95%CI: 0.79-0.99), homozygote model (OR = 0.82, 95%CI: 0.70-0.98) and additive model (OR = 0.90, 95%CI: 0.83-0.97). In addition, a significant association was observed between the IFNGR1 rs7749390 polymorphism and TB susceptibility among Africans in allele model (OR = 0.89, 95%CI: 0.82-0.98). No significant association was found between the IFNGR1 rs1327474 polymorphism and TB susceptibility. In summary, IFNGR1 rs2234711 polymorphism was associated with increased TB susceptibility in Africans and decreased TB susceptibility in Asians, while IFNGR1 rs7749390 polymorphism was associated with decreased TB susceptibility in Africans.